2005
DOI: 10.1164/rccm.200503-439oc
|View full text |Cite
|
Sign up to set email alerts
|

3p Microsatellite Alterations in Exhaled Breath Condensate from Patients with Non–Small Cell Lung Cancer

Abstract: The still-high mortality for lung cancer urgently requires the availability of new, noninvasive diagnostic tools for use in early diagnosis and screening programs. Recently, exhaled breath condensate (EBC) has been proposed as a useful tool to obtain biological information on lung cancer disease. This study provides, for the first time, evidence that DNA alterations already described in lung cancer are detectable in EBC from patients with non-small cell lung cancer (NSCLC) and in healthy subjects. Thirty patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
70
0
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 77 publications
(74 citation statements)
references
References 31 publications
(45 reference statements)
3
70
0
1
Order By: Relevance
“…It has been reported that a significantly greater proportion of patients with non-small cell lung cancer have 3p microsatellite alterations or loss of heterozygosity in EBC compared to controls [ 173 ], with overlapping profiles of microsatellite alterations in DNA from EBC and tumour tissues [ 174 ]. It has also been demonstrated that p53 mutations are present in EBC of patients with lung cancer, while no mutations were found in controls [ 175 ].…”
Section: Exhaled Breath Dnamentioning
confidence: 99%
“…It has been reported that a significantly greater proportion of patients with non-small cell lung cancer have 3p microsatellite alterations or loss of heterozygosity in EBC compared to controls [ 173 ], with overlapping profiles of microsatellite alterations in DNA from EBC and tumour tissues [ 174 ]. It has also been demonstrated that p53 mutations are present in EBC of patients with lung cancer, while no mutations were found in controls [ 175 ].…”
Section: Exhaled Breath Dnamentioning
confidence: 99%
“…gefitinib or erlotinib) has been stressed [1,2]. Interestingly, our group has already shown that the exhaled breath condensate (EBC) can be a useful and noninvasive way to collect biological samples derived from high up and deep within the airways [3,4]. EBC has been demonstrated to be informative on molecular alterations of nonsmall cell lung cancer (NSCLC) and to characterise the oxidative and inflammatory process in the airways/lung [5,6].…”
Section: Exhaled Breath Condensate Is Not Suitable To Detect Egfr Sommentioning
confidence: 99%
“…In particular, staining for proliferation cell nuclear antigen marker and Ki-67 proliferation marker increases with increasing atypia when a decrease of the tumor suppressor factor FHIT is demonstrated. The latter factor has been involved in tumor initiation and progression of several cancers including those of the lung (33). In addition, the progressive accumulation of p53 expression does not parallel the expression of another member of the p53 signaling pathway, namely p21.…”
Section: Discussionmentioning
confidence: 99%